2006
DOI: 10.1038/sj.jp.7211495
|View full text |Cite
|
Sign up to set email alerts
|

Does birth weight discordance in preterm twins affect neonatal outcome?

Abstract: Objective: To compare neonatal morbidity and mortality between hospitalized discordant and concordant preterm twin pairs.Study Design: This was a retrospective, hospital-based study of preterm twins, followed in neonatal intensive care unit. Twins were classified as discordant when the difference in birth weight was >15%. Morbidity and mortality rates were compared between discordant and concordant groups.Results: Of 136 preterm twins in the study, 54 were discordant and 82 were concordant. In discordant twins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…Three studies (7468 twins) explored the risk of composite neonatal morbidity in twins compared with those without a BW discordance ≥15% (Figure ) . When considering all twin pregnancies, the risk of composite morbidities was higher in twins with compared to those without a BW discordance ≥15% (OR 1.4, 95% CI 1.0‐1.9; I 2 = 52%, P = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (7468 twins) explored the risk of composite neonatal morbidity in twins compared with those without a BW discordance ≥15% (Figure ) . When considering all twin pregnancies, the risk of composite morbidities was higher in twins with compared to those without a BW discordance ≥15% (OR 1.4, 95% CI 1.0‐1.9; I 2 = 52%, P = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies that examined this population have shown that multifetal gestations with discordant but appropriatefor-gestational age growth are not at increased risk of fetal or neonatal morbidity and mortality (93)(94)(95)(96). Several studies that examined this population have shown that multifetal gestations with discordant but appropriatefor-gestational age growth are not at increased risk of fetal or neonatal morbidity and mortality (93)(94)(95)(96).…”
Section: Are Multifetal Gestations With Discordant Fetal Growth At Rimentioning
confidence: 99%
“…Newborns who have a high-risk of hypoglycemia and need of hypoglycemia screening in the first hour of life [22] are newborns who weigh more than 4 kg or less than 2 kg, large for gestational age (LGA) infants who are above the 90th percentile, small for gestational age (SGA), infants below the 10th percentile [23], and infants with intrauterine growth restriction [24][25][26][27][28][29][30][31]. In addition, high risk newborns are children with gestational age less than 37 weeks, children with sepsis [32] or born to a mother having chorioamnionitis or toxemia.…”
Section: High Risk Neonatesmentioning
confidence: 99%